Applications of high pressure to pre-rigor rabbit muscles affect the functional properties associated with heat-induced gelation. (July 2017) - Xue, Siwen; Yang, Huijuan; Liu, Rui; Qian, Chang; Wang, Mengyao; Zou, Yufeng; Xu, Xinglian; Zhou, Guanghong
Abstract: High pressure (HP) was applied to pre-rigor rabbit muscles (PRRMs) for the manufacture of value-added gel-type products. A 2 × 3 factorial design was adopted for HP-treatment (100, 200 and 300 MPa for 15 or 180 s) to PRRMs. The HP-treated meat was used for gel preparation and determination of water mobility properties and textural profiles. Salt-soluble meat proteins (SSMP) were then extracted from meat for estimating the tertiary conformational changes (hydrophobic and sulfhydryl groups). The water-holding capacity of treated samples increased significantly ( P  < 0.05) except for those treated at 300–180 (MPa-s). The hardness, cohesiveness and chewiness were significantly improved ( P  < 0.05) by moderate HP-treatments (100–200 MPa for 15 or 180 s). HP-induced the de-polymerization of some protein components, together with unfolding and refolding of protein tertiary conformations, partly explaining the observed functionality changes. In conclusion, application of moderate HP to PRRM modified the protein conformation in a manner that improved the functional properties of gels. Highlights: Applying various HPP to PRRMs modified the muscle proteins differently. Slight reduction of SSMP solubility occurred in the samples underwent HPP. Protein components were altered by HPP as shown in salt-soluble muscle proteins. Defined HPP modified SSMP in a manner that improves its gelation properties. HP level higher than 200 MPa was detrimental to the gelation properties.